Hormati Orang Tuamu : Relavansi Keluaran 20:12 Di Tengah Kehidupan Modern - Andeas Laoli; Malik Bambangan (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The fifth commandment in the Ten Commandments, "Honor your father and your mother," found in Exodus 20:12, remains relevant in modern life despite the various social, cultural, and technological changes society has undergone. This research employs a qualitative literature approach to explore the meaning and significance of honoring parents in contemporary contexts. An analysis of theological, sociological, and Christian ethical literature demonstrates that honoring parents is not only a religious obligation but also contributes positively to the well-being of families and communities. This value helps maintain intergenerational relationships, strengthens family bonds, and supports social stability. In the modern era, challenges such as individualism, globalization, and technological advancement often affect the interactions between children and parents. Nevertheless, the essence of respect as a moral and social responsibility remains significant. This study also highlights how the principle of honoring can be adapted to modern conditions without losing its original meaning. Such respect encompasses care, attention, and appreciation, which continue to be relevant in contemporary contexts.